Leucaena hedgerow intercropping and cattle manure application in the Ethiopian highlands. II. Maize yields and nutrient uptake - Lupwayi, N.Z.; Haque, I.; Saka, A.R.; Siaw, D.E.K.A. (Springer, 1998)
The effects of Leucaena leucocephala and L. pallida prunings and cattle manure on maize nutrient uptake and yield were investigated in a hedgerow inter-cropping trial in the Ethiopian highlands. Hedgerow inter-cropping (also called alley cropping) is an agroforestry system in which trees are grown in dense hedges between alleys where short-cycle crops are grown. The hedges are pruned periodically during the cropping period and the prunings are added to the soil as green manure. For each leucaena species, the experiment had 16 treatments resulting from a factorial combination of four levels of leucaena leaf prunings (no prunings applied: first prunings applied; first and second prunings applied: first, second and third prunings (no prunings applied: first prunings applied; first and second prunings applied: first, second and third prunings applied), two levels of air-dried cattle manure (0 and 3 t dry matter ha-1 and two levels of N fertilizer (0 and 40 kg N ha-1 as urea). Uptake of N, P and K increased significantly with application of the three nutrient sources, but uptake of Ca and Mg either did not respond or decreased with application of prunings and manure. All the three factors increased maize grain and stover yields significantly, usually with no significant interactions between the factors. At least two applications of prunings were required to significantly increase nutrient uptake and maize yield. Maize in the row closest to the hedge did not respond to these nutrient inputs. It is concluded that hedgerow intercropping, with or without manure application, can increase crop yields moderately (to 2-3 t ha-1 maize grain yields) in the highlands, but P, Ca and Mg may have to be supplied from external sources if they are deficient in the soil. Additional N is still required for higher yields (>4 t ha-1 maize grain yields). However, quantification of the competition effects of the trees is also required to confirm these results.